Appropriateness of Content and Language in Class VII of Indonesian Language Worksheets based on the Merdeka Curriculum - Agustin, Indri Arti; Sjafei, Irna; Lubis, Winaria (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The companion book needed by students to support educational facilities is the Students’ Worksheet. The purpose of this study was to analyze the appropriateness of the content and language contained in the Indonesian Students’ Worksheet book for the second-grade students on first semester. The researcher used a quantitative descriptive method and content analysis. The data collection is Indonesian Students’ Worksheet in first semester. The data collection technique is carried out by documenting the appropriate aspects of the content and language. This time the research used descriptive statistical analysis techniques. Acquisition of content feasibility scores obtained a percentage of 91.66% while acquisition of language feasibility scores obtained a percentage of 79.76%. Eligibility of the content and language of Class 2 SMP first semester Indonesian Students’ Worksheet published by Putra Nugraha can be used for a companion book for Indonesian language textbooks for SMP/MTs/Package B grade VII semester 1 for the Merdeka Curriculum. This research can be continued in depth from the aspects of graphics, usability, and other types of research approaches